A Novel EOG based Synchronous and Asynchronous Visual Keyboard System - Saravanakumar, D; Vishnupriya, R; Reddy, M Ramasubba (IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI ...) (Online), 2019)
In this study, a high performance electrooculogram (EOG) based synchronous and asynchronous visual keyboard system is designed with large number of targets. The proposed system overcomes the limitations in the conventional EEG based visual keyboard system which has to compromise with either accuracy or typing speed of the system. In this study, we first proposed a synchronous visual keyboard system with 36 targets which includes alphabets, numbers and space. Later, we proposed an asynchronous visual keyboard system where the user can have control on the system. Ten subjects were taken for evaluating the performance of the proposed keyboard systems. A cue guided online experimental procedure was conducted on all the subjects in synchronous and asynchronous case. The average classification accuracy of 94.2% and 98.79% were obtained in synchronous and asynchronous cases respectively. Four subjects show 100% accuracy in the asynchronous case with average information transfer rate (ITR) of 66.71 bits/minute. This result shows that the developed system outperforms conventional keyboard system.